IMPLEMENTASI STRATEGI BADAN PENDAPATAN DAERAH DALAM MENINGKATKAN PAJAK AIR TANAH DI KOTA PEKANBARU (STUDI KASUS PAJAK AIR TANAH HOTEL DAN WISMA) - Annisa Irhamni; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Badan Pendapatan Daerah (BAPENDA) of Pekanbaru City is the agency authorized to collect groundwater tax. With the given authority, of course, regional income from groundwater taxes can be managed so as to achieve maximum results. Bapenda's strategies in increasing groundwater tax which summarized in Catur Cita Bapenda based on Stategic Planning Bapenda Pekanbaru City 2017-2022 are: (1) Upgrading the database (re-data collection), (2) Developing information technology, (3) Increasing human resources, and (4) Improving facilities and infrastructure. The purpose of this study is to analyze the implementation strategy of Bapenda in increasing the groundwater tax in Pekanbaru City as well as the constraints faced by Bapenda Pekanbaru City in implementing the strategy. This type of research is a descriptive study with a qualitative approach and the required data, both primary and secondary data, are obtained through observation, interviews, and documentation and then analyzed based on the research problem.The results of this study indicate that: First, the implementation of Bapenda's strategy in increasing groundwater tax in Pekanbaru City in this study is that the implementation of strategies in increasing groundwater tax has not been maximally implemented yet. Second, the inhibiting factors for the implementation of the Bapenda's Strategy in increasing groundwater tax are the lack of technical capacity of human resources, the unavailability of groundwater flow measurement facilities, and the lack of public understanding and awareness regarding groundwater tax in Pekanbaru City. Keywords: Implementation Strategy, Groundwater Tax